EXAMINING FACTORS INFLUENCING DRUG USE BY PERSONS SERVING A SENTENCE OF IMPRISONMENT IN THE STARA ZAGORA PRISON - Krasimira Benkova; Nadya Vlaeva; Vesela Mareva; Yavor Georgiev; Ekaterina Georgieva (Science & Research, 2022)

(untitled)
This article presents the results from the first two stages of a research project titled “Drug Abuse and Risk Groups. Studying the Three-Component Relationship Gender - Type of Psychoactive Substances Used - Type of the Crime Committed, in Prisoners”. The project is implemented by a research team at the Department of Social Work, Faculty of Medicine, Trakia University, Stara Zagora. Conducting of this research was inspired by the rise in the drug use among prisoners and the growing number of crimes committed either under the influence of drugs or in order to obtain money for buying drugs. The purpose of this article is to analyze the factors influencing drug use among prisoners in the Prison of Stara Zagora. An empirical research study has been conducted by means of a survey questionnaire, involving 122 prisoners. The results from the research study have brought out the significance of the general prevention as a factor influencing drug use among prisoners. On these grounds recommendations are made with regard to these persons for the benefit of the social work practice.